IMPLEMENTATION OF ENGLISH LEARNING AT DALWA ISLAMIC BOARDING SCHOOL IN THE 5.0 ERA FOR GENERATION Z - Kuswanto, Welly (Jurnal Pendidikan Islam, 2023)
This research explores the urgency of implementing English language learning at the Dalwa Islamic Boarding School in the 5.0 era, focusing on preparing Generation Z to face global challenges. Era 5.0 brings paradigmatic changes, requiring strategic renewal in traditional Islamic educational institutions such as the Dalwa Islamic Boarding School. This study uses a qualitative approach with a case study design. The research results show that the implementation of English language learning at the Dalwa Islamic Boarding School has high urgency. Apart from improving students' English skills, this learning also has a positive impact on the development of critical, collaborative and creative thinking skills. Research implications include recommendations for curriculum development, teaching staff in madrasas, and investment in technology-based English learning facilities. By integrating Islamic values, the Dalwa Islamic Boarding School can play a crucial role in producing a generation that is able to compete globally, while maintaining a strong Islamic identity.